An Academic Needs Analysis of Students in Micro Teaching Classes: Insights from Lecturers and Students at UNIQHBA - Hasbullah Hasbullah; I Wayan Suasta; I Wayan Suwirye; Irpan Irpan (MASI Mandiri Edukasi, 2026)
Microteaching plays a crucial role in preparing student-teachers to become effective educators by bridging theoretical knowledge and practical classroom skills. However, students often face significant challenges in applying pedagogical theories to real teaching contexts, particularly within faith-based and multilingual settings such as UNIQHBA. This study aims to identify and analyze the academic needs of students in microteaching classes by examining the perspectives of both students and lecturers. A qualitative research method was employed, utilizing semi-structured interviews, focus group discussions, and non-participant classroom observations with final-year education students and microteaching lecturers. The findings reveal key academic needs, including difficulties in lesson planning and time management, challenges in using instructional English, low teaching confidence, inadequate feedback mechanisms, and limited access to teaching resources. These results indicate a persistent gap between pedagogical theory and actual classroom practice. The study concludes that microteaching programs require redesign to incorporate scaffolded practice, structured reflection, and improved resource availability.